Development and Implementation of Interactive e-Module using Microsoft Sway to Improve Disaster Literacy Skills - Platini, Laurensia Trimeta; Abdurrahman, Abdurrahman; Lengkana, Dewi (FKIP Universitas Lampung, 2022)
Disaster literacy needs to be introduced to provide understanding to students and minimize disaster risk. The purpose of this study was to determine the use of an interactive emodule based on Microsoft Sway which is valid and effective in increasing students’ literacy. The design of this study uses a 4D (four-D) Research dan Development (R&D) model. The research sample consisted of control and experimental classes with instruments in the form of test instruments, questionnaires, and interviews. Data analysis was based on n-gain data, effect size, and descriptive percentages of teacher and student responses. The percentages of construct, content, and language validation obtained were 84.68%,80.58%, and 86% respectively, with all valid criteria. The study findings indicate that the use of an interactive e-module based on Microsoft Sway is valid and highly effective in improving students’ disaster literacy skills.Keywords: Interactive e-module, disaster literacy skills, disaster literacy, Microsoft Sway. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp854-871